Data analytics for pandemics : a COVID-19 case study - Shinde, Gitanjali Rahul, 1983-; Kalamkar, Asmita Balasaheb; Mahalle, Parikshit N.; Dey, Nilanjan, 1984- (Boca Raton, FL : CRC Press, 2021)
"Epidemic trend analysis, timeline progression, prediction and recommendation are critical for initiating effective public health control strategies and AI and data analytics play an important role in epidemiology, diagnostic and clinical fronts. The focus of this book is data analytics for COVID-19 which includes an overview of COVID-19 in terms of epidemic/pandemic, data processing and knowledge extraction. Data sources, storage and platforms are discussed along with discussion on data models, their performance, different Big data techniques, tools and technologies. This book also addresses the challenges in applying analytics to pandemic scenarios, case studies and control strategies"--
OCLC-licensed vendor bibliographic record.
Keywords: COVID-19 (Disease) -- Statistical methods; COVID-19 (Disease) -- Data processing; COVID-19 (Disease) -- Forecasting; Big data